Differential response at the seafloor during Palaeocene and Eocene ocean warming events at Walvis Ridge, Atlantic Ocean (ODP Site 1262). (20th December 2016) - Deprez, Arne; Jehle, Sofie; Bornemann, André; Speijer, Robert P.
Abstract: The Latest Danian Event (LDE, c . 62.1 Ma) is an early Palaeogene hyperthermal or transient (<200 ka) ocean warming event. We present the first deep‐sea benthic foraminiferal faunal record to study deep‐sea biotic changes together with new benthic ( Nuttallides truempyi ) stable isotope data from Walvis Ridge Site 1262 (Atlantic Ocean) to evaluate whether the LDE was controlled by similar processes as the minor early Eocene hyperthermals. The spacing of the double negative δ 13 C and δ 18 O excursion and the slope of the δ 18 O–δ 13 C regression are comparable, strongly suggesting a similar orbital control and pacing of eccentricity maxima as well as a rather homogeneous carbon pool. However, in contrast to early Eocene hyperthermals, the LDE exhibits a remarkable stability of the benthic foraminiferal fauna. This lack of benthic response could be related to the absence of threshold‐related circulation changes or better pre‐adaptation to elevated deep‐sea temperatures, as the LDE was superimposed on a cooling trend, in contrast to early Eocene warming.